ANALISIS FAKTOR FOREIGN LANGUAGE ANXIETY PADA SILENT LEARNERS DALAM PEMBELAJARAN MAHARAH KALAM MAHASISWA PENDIDIKAN BAHASA ARAB SEMESTER 4 DAN 2 DI UIN K.H. ABDURRAHMAN WAHID PEKALONGAN - Ulwiyah, Nur; Muyassaroh, Nurul; Karimah, Khikmatul; Muhajir, Nirmalasari; Syukron, Akhmad Aufa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the factors contributing to foreign language anxiety (FLA) among reticent students during speaking skills maharah kalam instruction at an Arabic language school. The study was motivated by observations that these students exhibited passivity, a reluctance to speak, and anxiety when using Arabic in the classroom. A qualitative approach with a descriptive design was employed. Data were collected through observations and interviews with two speaking skills instructors and three reticent students. The Miles, Huberman, and Saldaña model comprising data reduction, data display, and conclusion drawing was used for data analysis. The results indicate that both internal and external factors influence foreign language anxiety among reticent students. Internal factors include a lack of self-confidence, fear of making mistakes, a tendency to overthink, and prior learning experiences. External factors include the absence of an Arabic-speaking environment (*bi'ah lughawiyah*), fear of negative criticism, social comparison with peers, and academic demands associated with speaking skills instruction. The findings reveal that the two primary factors driving foreign language anxiety in these students are a lack of self-confidence and the absence of an Arabic-speaking environment. It is hoped that this study will assist instructors in devising teaching strategies that enhance the learning environment and encourage students to use Arabic actively.